2009
DOI: 10.1111/j.1540-8167.2008.01415.x
|View full text |Cite
|
Sign up to set email alerts
|

Avoid Delivering Therapies for Nonsustained Fast Ventricular Tachyarrhythmia in Patients with Implantable Cardioverter/Defibrillator: The ADVANCE III Trial

Abstract: The ADVANCE III trial is the first randomized investigation evaluating the reduction of ICD Rx for fast VT due to a prolongation of NID in a general ICD patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Patients were randomized to the standard-detection programming used in the PainFREE II trial 14 (18/24 intervals) or to long-detection programming (30/40 intervals). 16 A VT zone was programmed when a slow VT with CL > 320 ms had previously been recorded; therapy programming was tailored by the physician to the recorded VT.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were randomized to the standard-detection programming used in the PainFREE II trial 14 (18/24 intervals) or to long-detection programming (30/40 intervals). 16 A VT zone was programmed when a slow VT with CL > 320 ms had previously been recorded; therapy programming was tailored by the physician to the recorded VT.…”
Section: Methodsmentioning
confidence: 99%
“…By prolonging the time of detection to longer settings, it is not surprising that fewer inappropriate therapies were delivered; previous studies have shown that most inappropriate therapies are determined by high-rate conducted atrial arrhythmias or lead noises, both of which are influenced favorably by a longer NID. [7][8][9][10][11][12][13][14][15][16] Nevertheless, in terms of the recent hypothesis of a possible association between unnecessary ATPs and increased risk of adverse events in PP, the present data provide a clear indication for a programming strategy that can safely reduce inappropriate therapies in SP patients as well.…”
Section: Inappropriate Therapiesmentioning
confidence: 95%
“…11 Continuous data were described as means and SDs, whereas categorical data were expressed as counts and percentages. Follow-up duration was reported as median and 25th to 75th percentiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the long detection arm there was an 81% reduction in shocks and significantly fewer "inappropriate" detections for non-sustained atrial tachyarrhythmia. We await ADVANCE III [39] a prospective randomised comparison of 30/40 with 18/24 detection, aiming to reduce shocks for non-sustained arrhythmia in the FVT zone (CL ≤ 320 ms). The subjects are primary and secondary prevention ICD recipients.…”
Section: Extending Detection Intervals For Reducing Inappropriate Thementioning
confidence: 99%